To investigate the effect of a fish oil containing parenteral lipid emulsion on inflammatory markers, gas exchange and clinical outcomes in septic patients - Donoghue, Veronique (Stellenbosch : Stellenbosch University, 2018)
Thesis (MNutr)--Stellenbosch University, 2018.